2006
DOI: 10.2337/db05-1647
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Deficiency Exacerbates Islet Cell Dysfunction After β-Cell Injury

Abstract: The cause of cystic fibrosis-related diabetes (CFRD) remains unknown, but cystic fibrosis transmembrane conductance regulator (CFTR) mutations contribute directly to multiple aspects of the cystic fibrosis phenotype. We hypothesized that susceptibility to islet dysfunction in cystic fibrosis is determined by the lack of functional CFTR. To address this, glycemia was assessed in CFTR null (CFTR ؊/؊ ), C57BL/6J, and FVB/NJ mice after streptozotocin (STZ)-induced ␤-cell injury. Fasting blood glucose levels were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…Alternatively, a more direct role for CFTR in the regulation of the endocrine pancreas has been proposed (35,36). Our above results demonstrating a correlation between hyperglycemia onset and histopathologic damage to the CF pancreas supports the bystander damage hypothesis (Figures 1-3), but does not disprove potential involvement of CFTR in regulating the endocrine pancreas.…”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…Alternatively, a more direct role for CFTR in the regulation of the endocrine pancreas has been proposed (35,36). Our above results demonstrating a correlation between hyperglycemia onset and histopathologic damage to the CF pancreas supports the bystander damage hypothesis (Figures 1-3), but does not disprove potential involvement of CFTR in regulating the endocrine pancreas.…”
Section: Figuresupporting
confidence: 77%
“…Furthermore, to our knowledge, no clinical studies have evaluated CF glucose abnormalities in the first years of life. Cftr-knockout mice demonstrate enhanced sensitivity to low-dose streptozotocin-induced hyperglycemia, but are euglycemic in the absence of streptozotocin (35,36). The recent development of CFTR-knockout models in the pig and ferret provides new avenues for investigating the pathogenesis of CFRD.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports a function for CFTR in pancreatic islets where, in rats, investigators have identified CFTR mRNA (20). In mice made diabetic by streptozotocin, those who were CFTR-null (Ϫ/Ϫ) had higher blood glucose levels than other mice; the investigators concluded that islet dysfunction is inherent to the CFTR Ϫ/Ϫ state (21). CFTR has also been identified in the human hypothalamus, (22), where it may play a role in glucose regulation.…”
Section: Risk Factorssupporting
confidence: 58%
“…Unlike previous reports where CFTR-deficient mice showed an exacerbation of STZ-induced hyperglycemia, our findings showed no difference between STZ-treated CFKO and WT mice (38). The rationale for these differences is likely a result in the variations of STZ treatment regimens.…”
Section: Discussioncontrasting
confidence: 56%